2020
DOI: 10.33448/rsd-v9i3.2447
|View full text |Cite
|
Sign up to set email alerts
|

O uso do Teste de Alfabetização Científica Básica em estudantes do Ensino Fundamental: análise da confiabilidade de medida nesse grupo

Abstract: Measuring Scientific Literacy allows us to evaluate how this construct can be perceived in the numerous activities that aim to promote it. The Basic Scientific Literacy Test consists of a questionnaire with great potential to measure the level of this concept. However, the literature points out research that makes use of this instrument, which was elaborated for graduates of Basic Education, in elementary school students. Thus, the problem of this study aims to analyze the psychometric characteristics of its i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 6 publications
0
4
0
3
Order By: Relevance
“…Among the 18 studies that adopted the TBSL and its versions-TACB, TACB-S, TACB-R, and adapted -, Camargo et al (2011), Gresczysczyn et al (2018), Laugksch and Spargo (1996a), Lima and Garcia (2015), Oliveira and Silva-Forsberg (2012), Rivas et al (2017), Vizzotto andDel Pino (2020a, 2020b), and Vizzotto and Mackedanz (2018) revealed that most of the students assessed are scientifically literate. The studies of Sousa (2019a, 2019b), Laugksch and Spargo (1999), Lima and Garcia (2013), Nascimento-Schulze (2006), Vizzotto (2019), and Vizzotto et al (2020, on the other hand, revealed that the majority of the students assessed did not reach the minimum number of hits required to be considered scientifically literate. The research of Özdem et al (2010) showed moderate scientific literacy scores of the investigated students, while that of Nascimento-Schulze et al (2006) indicated that there is a relationship between satisfactory performances on the TACB-R and high interest in scientific topics, as well as good grades and school attendance.…”
Section: Study Results: Performance In Scientific Literacy Assessmentmentioning
confidence: 99%
See 3 more Smart Citations
“…Among the 18 studies that adopted the TBSL and its versions-TACB, TACB-S, TACB-R, and adapted -, Camargo et al (2011), Gresczysczyn et al (2018), Laugksch and Spargo (1996a), Lima and Garcia (2015), Oliveira and Silva-Forsberg (2012), Rivas et al (2017), Vizzotto andDel Pino (2020a, 2020b), and Vizzotto and Mackedanz (2018) revealed that most of the students assessed are scientifically literate. The studies of Sousa (2019a, 2019b), Laugksch and Spargo (1999), Lima and Garcia (2013), Nascimento-Schulze (2006), Vizzotto (2019), and Vizzotto et al (2020, on the other hand, revealed that the majority of the students assessed did not reach the minimum number of hits required to be considered scientifically literate. The research of Özdem et al (2010) showed moderate scientific literacy scores of the investigated students, while that of Nascimento-Schulze et al (2006) indicated that there is a relationship between satisfactory performances on the TACB-R and high interest in scientific topics, as well as good grades and school attendance.…”
Section: Study Results: Performance In Scientific Literacy Assessmentmentioning
confidence: 99%
“…Among the research that used the pilot study data, Brossard and Shanahan (2006), Laugksch and Spargo (1996a), Rundgren et al (2010), Soobard andRannikmäe (2011), andWenning (2007) indicated the process of designing and validating scientific literacy assessment instruments, Rachmatullah et al (2016) performed the translation of the SLA into the local language in Indonesia, and Vizzotto et al (2020) analyzed the validity of the TACB-S for a different audience than the one for which it was designed.…”
Section: Methodological and Contextual Characteristics Of The Selecte...mentioning
confidence: 99%
See 2 more Smart Citations
“…Observando o elevado número de aplicações do TACB no 3.° ciclo do Ensino Básico, Vizzotto et al (2020) analisaram as características psicométricas deste instrumento, por meio da aplicação do TACB-S, a fim de verificar as suas validade e confiabilidade para esse nível de ensino. Os resultados revelaram valores baixos de confiabilidade, de índices de dificuldade e de discriminação.…”
Section: Características Metodológicas E Contextuais Dos Estudos Sele...unclassified